RANCANG BANGUN APLIKASI PENJUALAN BUSANA WANITA BERBASIS WEB PADA TOKO NINETYNINE - Sulistiyono Sulistiyono; Saleh Dwiyatno; Rizki Fatullah; Andri Ramadhan (Teknik Informatika Fakultas Ilmu Komputer, 2020)
Ninetynine store is a trading business engaged in women's fashion that sells a wide range of teenage to adult women's clothing that has been established since 2014 until now and is located in Ramayana City of Serang. Currently the sales media used at Ninetynine stores are with social media such as Instagram and WhatsApp or come directly to the store. This is still considered lacking in increasing the high mobility available to customers. Existing sales transactions are still recorded manually, starting processing report data such as reports on transaction results and recording of goods to be sold which are only copied on the book because there is no media interface / interface in the form of a website as a place to sell the products in the store. Therefore it is possible to make a web-based women's clothing sales application. This application was built using the prototype method, using the PHP and MySQL programming languages ​​as a database. This website-based application aims to help shop managers make reports on women's clothing sales transactions and women's clothing data reports and is expected to provide convenience when purchasing women's clothing for the public.